Cystathionine‐gamma‐lyase overexpression in T cells enhances antitumor effect independently of cysteine autonomy. Issue 5 (12th March 2021) - Lancien, Melanie; Gueno, Lucile; Salle, Sonia; Merieau, Emmanuel; Beriou, Gaelle; Nguyen, Tuan H.; Abidi, Ahmed; Dilek, Nahzli; Solomon, Pierre; Poschmann, Jeremie; Michielin, Olivier; Vuillefroy de Silly, Romain; et al.
Abstract: T cells could be engineered to overcome the aberrant metabolic milieu of solid tumors and tip the balance in favor of a long‐lasting clinical response. Here, we explored the therapeutic potential of stably overexpressing cystathionine‐gamma‐lyase (CTH, CSE, or cystathionase), a pivotal enzyme of the transsulfuration pathway, in antitumor CD8 + T cells with the initial aim to boost intrinsic cysteine metabolism. Using a mouse model of adoptive cell transfer (ACT), we found that CTH‐expressing T cells showed a superior control of tumor growth compared to control T cells. However, contrary to our hypothesis, this effect was not associated with increased T cell expansion in vivo or proliferation rescue in the absence of cysteine/cystine in vitro. Rather than impacting methionine or cysteine, ACT with CTH overexpression unexpectedly reduced glycine, serine, and proline concentration within the tumor interstitial fluid. Interestingly, in vitro tumor cell growth was mostly impacted by the combination of serine/proline or serine/glycine deprivation. These results suggest that metabolic gene engineering of T cells could be further investigated to locally modulate amino acid availability within the tumor environment while avoiding systemic toxicity. Abstract : Gene engineering of T cells represents a promising approach for overcoming the aberrant metabolic milieu of solid tumors. Here, we found that overexpression of the transsulfuration pathway enzyme cystathionine‐gamma‐lyase (CTH, alias CSE or cystathionase) in antitumor T cells enhanced tumor growth control in vivo upon adoptive cell transfer. Unexpectedly, this effect was not associated with increased cysteine production by T cells but with decreased concentration of three other amino acids within the tumor interstitial fluid.